In Search Of Effectiveness Factors: A Case Study Of The UNIKL IIM E-Learning Portal - Tan, Wee Hoe (2006)
In 2004, the Universiti Kuala Lumpur Institut Infotech Mara (UniKL IIM) set up an e-learning portal called UniKL IIM E-Learning Portal. This portal was created based on an open source web based course management system - Claroline. After a year of implementation, a case study was carried out to identify the factors that determine the effectiveness of the e-learning portal.